2006
DOI: 10.5551/jat.13.267
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hyperlipidemia from Japanese Evidence

Abstract: The treatment of hyperlipidemia is aimed at preventing cardiovascular disease (CVD) and coronary heart disease (CHD). As the incidence of CHD in Japan is about one-third lower and that of stroke is two-fold higher compared to Western countries, and the doses of lipid-lowering drugs used in foreign randomized controlled clinical trials (RCTs) are much higher than in general use in Japan, it remains unclear whether the results of RCTs conducted in Western countries could be extrapolated to Japanese patients. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…The median triglyceride level decreased in all of the luseogliflozin groups. Because low HDL-C and hypertriglyceridemia are associated with increased risk of coronary heart disease 23 , the improvements in plasma lipids during treatment with luseogliflozin are expected to be beneficial for patients with T2DM, although these effects need to be confirmed in a longer study.…”
Section: Discussionmentioning
confidence: 99%
“…The median triglyceride level decreased in all of the luseogliflozin groups. Because low HDL-C and hypertriglyceridemia are associated with increased risk of coronary heart disease 23 , the improvements in plasma lipids during treatment with luseogliflozin are expected to be beneficial for patients with T2DM, although these effects need to be confirmed in a longer study.…”
Section: Discussionmentioning
confidence: 99%
“…18 Recently, it has also been reported that treatment with n-3 PUFA, a mixture of EPA and docosahexaenoic acid, ameliorates hepatic steatosis and necroinflammation in humans 19 and rats, 20 probably due to a reduction of hepatic tumor necrosis factor (TNF)-α expression and improvement of insulin sensitivity. However, the efficacy of single treatment of EPA for NASH patients has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of these actions are thought to include inhibition of platelet aggregation and improvement of blood rheologic properties 24) . In addition, some effects of EPA on serum lipids have been reported, as well as a unique preventive effect against atherosclerotic disease and coronary events [25][26][27] ; however, the influence of EPA on EDMPs, Ang-2 and adiponectin in diabetic patients is poorly understood. In the present study, we investigated the effect of EPA on EDMPs, Ang-2 and adiponectin in type 2 diabetes, focusing on the anti-thrombogenic and anti-atherosclerotic properties of EPA.…”
Section: Introductionmentioning
confidence: 99%